Pengaruh Bakteri Pelarut Fosfat Dan Bakteri Penambat Nitrogen terhadap Pertumbuhan Tanaman Tomat pada Tanah Masam - Yenni Widi Astuti; Lestanto Unggul Widodo; Iman Budisantoso (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
Acid soil is the dried soil which has great potential for growing of agriculture commodity but this kind of soil has not been used optimally. The acid soil which has acidity reaction at pH<5,0 has Al poisonous potency, less of organic material and sensitivity toward erosion, and also less of nitrogen (N) and phosphor (P). Those problems can be solved by doing phosphate-solubilizing bacteria and nitrogen fixing bacteria inoculation. The aims of this study were to know the effect of phosphate-solubilizing bacteria, nitrogen fixing bacteria, and the mixture of both of them to the wet weight, height, level of nitrogen and phosphor of tomato plants. This research was conducted experimentally for six weeks by using completely randomized design (CRD) with 4 treatments. One treatment is a treatment without bacteria inoculation and the other treatments used bacteria inoculations which were phosphate-solubilizing bacteria inoculation, nitrogen fixing bacteria inoculation, and the mixture of both of them inoculations. Data were analyzed by using analysis of variance (ANOVA) at the 95% and 99% confidence level. The result proved the mixture of phosphate-solubilizing bacteria and nitrogen fixing bacteria is the most effective inoculation to improve the wet weight, height, level of nitrogen, and level of phosphor of tomato plant in acid soil.